Enhancing Students’ Critical Thinking Skills through Philosophy of Science - Ucu Feni; Siti Fatimah (LANGGAM: International Journal of Social Science Education, Art and Culture, 2026)
This study investigates how the philosophy of science contributes to enhancing students’ critical thinking skills, focusing on its three foundational dimensions: ontology, epistemology, and axiology. While previous research has widely examined strategies for teaching critical thinking and the use of philosophical perspective in education, limited attention has been given to integrating these three philosophical dimensions into a single analytical framework for science education. To address this gap, a systematic literature review was conducted using academic journal articles, books, and empirical studies related to philosophical inquiry and critical thinking development. The findings show that ontological perspectives encourage students to question the nature of scientific reality and examine underlying assumptions, while epistemological insights help them understand how knowledge is constructed and justified, thereby strengthening analytical and reflective thinking. Axiological considerations further support students in recognizing the ethical and value-laden aspects of scientific inquiry, which guide them toward responsible and well-reasoned judgments. The novelty of this study lies in its integrative framework that unifies ontology, epistemology, and axiology to explain how philosophical literacy can systematically foster critical thinking in science education. This contribution provides a conceptual foundation for designing instructional approaches that explicitly incorporate philosophical inquiry to enhance students’ critical thinking abilities.